Hydrogen Sulfide Inhibits Bronchial Epithelial Cell Epithelial Mesenchymal Transition Through Regulating Endoplasm Reticulum Stress - Lin, Fan; Liao, Chengcheng; Zhang, Jinsheng; Sun, Yun; Lu, Weiwei; Bai, Yu; Liao, Yixuan; Li, Minxia; Qi, Yongfen; Chen, Yahong (Frontiers in Molecular Biosciences, 2022)
Epithelial mesenchymal transition (EMT) is a contributing factor in remodeling events of chronic obstructive pulmonary disease (COPD). Hydrogen sulfide (H2S) has been implicated in the pathogenesis of COPD, but the effect of H2S in regulating EMT and the underlying mechanisms is not clear. In this study, we assessed endoplasmic reticulum (ER) stress markers, EMT markers and associated signal molecules in rat lungs, bronchial epithelial cells and human peripheral lung tissues to investigate the effect of H2S in regulating EMT and the underlying mechanisms. We found that EMT and ER stress occurred in lung epithelial cells, especially in bronchial epithelial cells of smokers and COPD patients. In cigarette smoke (CS)-exposed rats, intraperitoneal injection of NaHS significantly alleviated CS-induced lung tissue damage, small airway fibrosis, ER stress and EMT, while intraperitoneal injection of propargylglycine (cystathionine-gamma-lyase inhibitor) aggravated these effects induced by CS. In the nicotine-exposed 16HBE cells, appropriate concentration of H2S donor not only inhibited nicotine-induced ER stress, but also inhibited nicotine-induced enhancement of cell migration ability and EMT. ER stress nonspecific inhibitors taurine and 4-phenyl butyric acid also inhibited nicotine-induced enhancement of cell migration ability and EMT. Both H2S and inositol requiring enzyme 1 (IRE1) activation inhibitor 4μ8C inhibited nicotine-induced activation of IRE1, Smad2/3 and EMT. These results suggest that H2S inhibits CS- or nicotine-induced ER stress and EMT in bronchial epithelial cells, alleviates CS-induced lung tissue damage and small airway fibrosis. The IRE1 signal pathway and Smad2/3 may be responsible for the inhibitory effect of H2S.